A discrete, two‐dimensional frictional contact model for dynamic contact between viscoelastic materials and rough counterparts. Issue 1 (17th December 2018) - Schulte, Frank; Sextro, Walter
Abstract: Friction between a viscoelastic material and a rough surface occurs in many technical applications, e. g. windshield wiper, rubber gaskets or the tire‐road contact. For the investigation of friction phenomena a detailed frictional contact model is necessary. The friction of viscoelastic materials is divided into the two main effects hysteresis friction and adhesion friction. Multiple influence factors on the friction behaviour are known, e. g. material properties of the contact partners, normal force, excitation frequency through the counterpart, as well as temperature. Due to the frictional forces a system is significantly influenced in its vibrational properties. For the simulation of the complex friction processes with viscoelastic materials, a two‐dimensional friction contact model with the assumption of an isotropic roughness has been developed. The model consists of a rough rigid and a rough viscoelastic layer. The rough rigid layer represents a measured roughness profile. Due to the low stiffness of the viscoelastic material, the counter body can be assumed to be rigid. The viscoelastic layer consists of a number of point‐masses with generalised Maxwell‐models and represents the viscoelastic material. By this model the normal and tangential contact can be simulated dynamically. Effects such as changing the contact status during the friction process are taken into account. A stiffening of the viscoelastic material and thus a lower real contact surface at higher excitation frequencies or low temperatures can be shown with the model. This is especially important for the calculation of adhesion friction, as it depends directly on the actual contact area.